Ações Criativas de um grupo de estudantes ao lidar com atividades de Modelagem Matemática. - Setti, Elenice Josefa Kolancko (2022)
The literature that covers Mathematical Modeling from the perspective of Mathematics Education largely corroborate the statement that performing Modeling activities can develop creativity in students or, alternatively, that creativity is a requirement for performing a Mathematical Modeling activity. However, previous research dedicated to investigate the connection between creativity and Mathematical Modeling show a gap when it comes to the pathway of students’ creative action when they are developing the activities. We therefore aimed to understand how the creative action occurs in Mathematics students dealing with Modeling activities in the context of a Mathematical Modeling I course offered in public university in western Paraná. The specifics goals of this study were to perform an analytical bibliographic review on Creativity in the context of Mathematical Modeling in perspective of Mathematics Education; and to understand the manifestations of students' creative actions when dealing with Mathematical Modeling activities. As theoretical support, we take the perspective of Vlad Glăveanu’s Cultural Psychology of Creativity, and Lev Vigotski’s Creative Imagination. Based on the results, we propose the thesis that, with respect to the student group analyzed, the creative action when dealing with Modeling activities is formed through interactions between students and between students and their mediator teachers. These interactions operate as triggers for the creative action or for the creation of an idea, as well as interventions that inhibit such action. It is from freedom - as a political, social, cultural and thought act made possible by the Modeling environment - that the need for investigation can be initiated in the students, in order to motivate them to work collaboratively in order to produce new artefacts and to give new meanings to existing artefacts.